The Effect of White Rot Fungus (Ganoderma sp) as Decomposers on Composting Using Combination of Cattle Feces and Water Hyacinth (Eichhornia crassipes) as Organic Matter - Muhammad Irfan Said; Effendi Abustam; Sitti Nurani Sirajuddin; Jamila; Tensi; Abdel Razzaq Al Tawaha; Abdel Rahman M. Al Tawaha (Baghdad Science Journal, 2022)
In Indonesia, cattle feces (CF) and water hyacinth (WH) plants are abundant but have not been widely revealed. The use of microorganisms as decomposers in the fermentation process has not been widely applied, so researchers are interested in studying further. This study was to evaluate the effect of the combination of CF with WH on composting by applying white-rot fungal (WRF) (Ganoderma sp) microorganism as a decomposer. A number of six types of treatment compared to R1(ratio of CF:WH)(25%:75%)+WRF; R2(ratio of CF:WH)(50%:50%)+WRF; R3(ratio of CF:WH)(75%:25%)+WRF; R4(ratio of CF:WH)(25%:75%) without WRF; R5(ratio of CF:WH)(50%:50%) without WRF; R6(ratio of CF:WH)(25%:75%) without WRF. The results showed that the use of WRF decomposers and organic matter (CF and WH) at different ratios affected the properties of compost such as pH value, C-organic, N-organic, C/N ratio, P2O5 and K2O compounds. The WRF decomposer significantly decreases to the pH value, and the C/N ratio, but increases the value of C-organic, N-organic, P2O5 and K2O. The properties of the compost produced are in accordance with the standards set by the Indonesian National Standard (INS) and the regulation of the Ministry of Agriculture of the Republic of Indonesia. The WRF was needed to consider as a decomposer in producing compost.  Based on the results of the study, it was concluded that the R1(CF: WH)(25%:75%)+WRF) treatment was the best ratio combination to produce compost using WRF (Ganoderma sp) as a decomposer with the best properties.